Miracle Grisslato - Polii, Yudistira S.; Sambentiro, Nadila; Sinolungan, Linda; Djamali, Rajab (Indo Consultan Energi, 2025)
The Food and Beverage industry sector in Indonesia continues to grow along with population growth. This study aims to create a new dessert innovation that combines Italian dishes, namely Gelato and Grissini, with local Indonesian flavors, specifically the typical red bean avocado ice (es brenebone) of North Sulawesi, called Miracle Grisslato. The research method uses observation and interviews to produce an attractive product that is acceptable to various groups. The results show that the combination of Gelato made from red beans and avocado with the flavor of es brenebone, served with crunchy Grissini, successfully creates a unique sensation of taste, texture, and aroma. The implication of this research is the creation of an innovative dessert dish that combines international cuisine with Indonesian flavors. For further development, it is recommended to improve the quality of ingredients and tools and minimize production costs, making the product more affordable and enjoyable for the wider community.